2019
DOI: 10.1080/14756366.2018.1488697
|View full text |Cite
|
Sign up to set email alerts
|

A mitochondrial-targeted peptide ameliorated podocyte apoptosis through a HOCl-alb-enhanced and mitochondria-dependent signalling pathway in diabetic rats and in vitro

Abstract: Mitochondria play important roles in the development of diabetic kidney disease (DKD). The SS peptide is a tetrapeptide that is located and accumulated in the inner mitochondrial membrane; it reduces reactive oxygen species (ROS) and prevents mitochondrial dysfunction. Podocytes are key cellular components in DKD progression. However, whether the SS peptide can exert renal protection through podocytes and the mechanism involved are unknown. In the present study, we explored the mechanisms of the SS peptide on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 44 publications
0
21
0
1
Order By: Relevance
“…SS peptides promote ATP synthesis, reduce electron leak and ROS production, and inhibit cardiolipin peroxidation [134], preventing the consequences of mitochondrial dysfunction, including apoptosis, inflammation, and NLRP3 inflammasome activation [134]. Specifically, SSP3 protected from experimental AKI [135] and in kidney injury in T1DM induced by streptozotocin in rats [136]. MitoQ, MitoTEMPO, or SkQR1 also reduced oxidative damage and renal inflammation [134,[137][138][139].…”
Section: Mitochondria-targeted Therapiesmentioning
confidence: 99%
“…SS peptides promote ATP synthesis, reduce electron leak and ROS production, and inhibit cardiolipin peroxidation [134], preventing the consequences of mitochondrial dysfunction, including apoptosis, inflammation, and NLRP3 inflammasome activation [134]. Specifically, SSP3 protected from experimental AKI [135] and in kidney injury in T1DM induced by streptozotocin in rats [136]. MitoQ, MitoTEMPO, or SkQR1 also reduced oxidative damage and renal inflammation [134,[137][138][139].…”
Section: Mitochondria-targeted Therapiesmentioning
confidence: 99%
“…[1][2][3] They currently underlie new drug developments, which will complement the existing therapies for cancer cells killing and cancer elimination. [4][5][6][7][8][9][10][11][12] The mitochondrial-targeting anti-cancer mechanisms include the activation of mitochondria-mediated apoptotic pathways via voltagedependent-anion-channel (VDAC) targeting agents or electron transport/respiratory chain blockers, [13][14][15] the increased induction of reactive oxygen species (ROS), 16,17 the inhibition of the Bcl-2 anti-apoptotic family of proteins, 18 the activation of the mitochondrial membrane permeability transition pore protein subunits, 19,20 the mtDNA targeting in cancer cells, 19 and treatments involving mitochondrial destabilization, mitochondrial membrane permeabilization, 21 mitochondrial fission and massive mitochondrial fragmentation using lipophilic cations targeting the inner membrane. [22][23][24][25][26][27][28] Hexokinase-II (HK-II) is increasingly regarded as an attractive therapeutic target for cancer therapy based on its key role in glycolysis as a part of the cell energy metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…SS31 peptide (H-D-Arg-Dmt-Lys-Phe-NH2) could specially concentrate in the inner mitochondrial membrane. It has been demonstrated that SS31 has excellent therapeutic efficacy in myocardial injury, neurodegeneration injury, and diabetic complications [710]. Our previous study demonstrated that mitochondria-targeted peptides (MTP131 and SPI20) could prevent contrast-induced acute kidney injury in rats [11].…”
Section: Introductionmentioning
confidence: 99%